Impact of time to surgery on mortality in hypotensive patients with noncompressible torso hemorrhage: An AAST multicenter, prospective study. Issue 5 (18th May 2022) - Duchesne, Juan; Slaughter, Kevin; Puente, Ivan; Berne, John D.; Yorkgitis, Brian; Mull, Jennifer; Sperry, Jason; Tessmer, Matthew; Costantini, Todd; Berndtson, Allison E.; Kai, Taylor; Rokvic, Giannina; et al.
Abstract : Patients who expired arrived to a trauma center in a similar time frame as did survivors. This suggests that even expediting a critically ill patient through the current trauma system is not sufficient time to save lives from NCTH. Abstract : BACKGROUND: Death from noncompressible torso hemorrhage (NCTH) may be preventable with improved prehospital care and shorter in-hospital times to hemorrhage control. We hypothesized that shorter times to surgical intervention for hemorrhage control would decrease mortality in hypotensive patients with NCTH. METHODS: This was an AAST-sponsored multicenter, prospective analysis of hypotensive patients aged 15+ years who presented with NCTH from May 2018 to December 2020. Hypotension was defined as an initial systolic blood pressure (SBP) ≤ 90 mm Hg. Primary outcomes of interest were time to surgical intervention and in-hospital mortality. RESULTS: There were 242 hypotensive patients, of which 48 died (19.8%). Nonsurvivors had higher mean age (47.3 vs. 38.8; p = 0.02), higher mean New Injury Severity Score (38 vs. 29; p < 0.001), lower admit systolic blood pressure (68 vs. 79 mm Hg; p < 0.01), higher incidence of vascular injury (41.7% vs. 21.1%; p = 0.02), and shorter median (interquartile range, 25–75) time from injury to operating room start (74 minutes [48–98 minutes] vs. 88 minutes [61–128 minutes]; p = 0.03) than did survivors. Multivariable Cox regression showed shorter time from emergency department arrival to operating room start was not associated with improved survival ( p = 0.04). CONCLUSION: Patients who died arrived to a trauma center in a similar time frame as did survivors but presented in greater physiological distress and had significantly shorter times to surgical hemorrhage intervention than did survivors. This suggests that even expediting a critically ill patient through the current trauma system is not sufficient time to save lives from NCTH. Civilian prehospital advance resuscitative care starting from the patient first contact needs special consideration. LEVEL OF EVIDENCE: Prognostic/Epidemiologic, Level III Abstract :